Soil erosion and smallholders' conservation decisions in the highlands of Ethiopia - Shiferaw Bekele; Holden, Stein (Elsevier, 1999)
Soil erosion is one of the most serious environmental problems in Ethiopia. Coupled with growing populations, falling per capita food production and worsening poverty, loss of productive land due to land degradation undermines rural livelihoods and national food security. Despite their awareness of the erosion problem, peasants' investments in land have been limited. We use an applied nonseparable model to simulate conservation decisions. Pervasive market imperfections, poverty and high rates of time preference seem to undermine erosion-control investments. Lack of technologies which provide quick returns to subsistence-constrained peasants also seem to deter such investments. Lower private incentives to internalize the intertemporal land degradation externality may require public intervention.